Changes in health‐related quality of life and activities of daily living after hip fracture because of a fall in elderly patients: a prospective cohort study. Issue 4 (27th February 2015) - Orive, M.; Aguirre, U.; García‐Gutiérrez, S.; Las Hayas, C.; Bilbao, A.; González, N.; Zabala, J.; Navarro, G.; Quintana, J. M.
Summary: Background: The impact of hip fracture because of a fall on health‐related quality of life (HRQoL) and activities of daily living (ADL) have not been well established. Aim: To evaluate changes in HRQoL and the ability to conduct ADL among patients with hip fracture because of a fall and to compare these changes with patients who did not fall and break a hip, adjusting by gender and age. Methods: Adults aged 65 or more who attended the emergency departments of seven public hospitals were recruited in a prospective double‐cohort study (fracture cohort, n  = 776; non‐fracture cohort, n  = 115). ADL and HRQoL were assessed at baseline (during the postfall hospitalisation or by telephone afterwards) and 6 months later using the Barthel Index and the Lawton Brody Index for ADL, and the Short Form Health Survey (SF‐12) and Western Ontario and McMaster Universities Osteoarthritis Index short form (WOMAC‐SF) for HRQoL. Results: Adjusting by gender, age and baseline status, a hip fracture was a strong predictor of decline in all outcomes measured except for mental quality of life among men (measured by SF‐12). Hip fracture patients younger than 74 years reported significantly more pain (measured by WOMAC‐SF) than the comparison group (p = 0.02), but this difference was not observed among older patients (p = 0.19 for 75–84 years; p = 0.39 for ≥ 85 years). Discussion: Hip fractures have profound effects on HRQoL and ADL in both men and women, regardless of age. This indicates the need for special follow‐up care of elderly hip fracture patients in the immediate and late postfracture periods.